Influence of endurance running on calcaneal bone stiffness in male and female runners - Lara, B.; Salinero, J. J.; Gutiérrez, J.; Areces, F.; Abián-Vicén, J.; Ruiz-Vicente, D.; Gallo-Salazar, C.; Jiménez, F.; Del Coso, J. (European Journal of Applied Physiology, 2016)
Purpose: The aim of this investigation was to determine the influence of endurance running on calcaneus bone stiffness in male and female runners. Methods: A total of 122 marathoners (longer distance runners, men = 101; women = 21) and 81 half-marathon and 10-km runners (shorter distance runners; men = 48; women = 33), competing in an international running event, underwent an ultrasonographic assessment of the right and left calcaneus. Calcaneus bone stiffness was estimated using the measurements of the speed of sound (SOS) and broadband ultrasound attenuation (BUA). Seventy-five age-matched sedentary people served as the control group. Results: Male and female longer distance runners and shorter distance runners presented higher values than sedentary counterparts in SOS (P < 0.05), and calcaneus stiffness (P < 0.05). Although there were no significant differences between longer distance and shorter distance runners in the ultrasonographic variables, longer distance runners presented greater effects size in SOS (1.00 vs 0.93 males; 1.10 vs 0.77 females), BUA (0.62 vs 0.25 males; 0.89 vs 0.20 females) and calcaneus stiffness (0.88 vs 0.66 males; 1.20 vs 0.60 females) than shorter distance endurance runners. Conclusion: Calcaneus bone stiffness was higher in all endurance runners compared to a sedentary control population. The volume of ground reaction forces which occur during endurance running might induce the adaptation of the calcaneus bone.